Discussion - Of Mr. Kunz's Paper on the Gems and Precious Stones of Mexico (see p. 55) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1902)
Edward Halse, Puerto Berrio, Colombia, S. A. (communication to the Secretary): I have read with much pleasure the interesting and valuable paper by Mr. Kunz, and hope that the following brief notes, gathered a few years ago, while a resident in Mexico City, may help to elucidate the subjcct: Turquoise.—This was known to the Aztecs as Xihuitl. Santiago Ramirez states that they found it in the Cerro Xicohtzonc, close to Atzcapatzalco, a suburb of the City of Mexico (compare page 59). Opal.—This was known to the ancient Mexicans, for they named it mezcuitlatt (compare page 63). Jade.—Under this was iucluded a third mineral, prehnite, not mentioned by Mr. Kunz. According to James D. Dana, part of the "jade " of China is prehnite; and Humboldt informs us, in his work on New Spain, that the same species of jade is known in some parts of Mexico as mahagua (majagua ?). The same writer says, in his Views of the Cordilleras, that the Aztec name Tecpatl included flint, hornstone, and green jade; and finally, in his Travels in South America," he discusses the nature of the ancient amazon-stones, and declares them to have been made out of a jade resembling " compact feldspar," one of the constituents of the gabbro verde di Corsica. IIence those stones were probably composed of nephrite. According to Humboldt, the form given to them most frequently is that of the Babylomian cylinder, longitudinally perforated, and loaded with inscriptions and figures. They were also cut by the natives into very thin plates, perforated at the center, suspended by a thread, and worn as amulets. According to the historian Clavijero, the specific name given by the Aztecs to the nephritic stone (jadeite) was Quitzalitztli,